SCIENTIFIC APPROACH : TEACHER'S BELIEFS AND PRACTICES IN AN ELT CONTEXT - Intani Pertiwi, - (2019)
Scientific Approach had been recommended by 2013 Curriculum for around five years to be used by teachers. However, in the field, the Scientific Approach does not get that much support to suit the language teaching. Many practitioners in English Teaching questioned the effectiveness and practicality of the approach to be implemented in language teaching. However, many English teachers still believed in this approach. Some of the English teachers were also still required to use this approach by the school authority they work to. This study was aimed at exploring what beliefs the English teachers had about Scientific Approach in ELT context and how those beliefs were reflected in their teaching. The main frameworks used in this study were the theory of beliefs suggested by Chan and Leung, some theories about the elements of Scientific Approach and some theories about the relationship between beliefs and practices. This study was a qualitative research using case study design which employed two English teachers as the participants. The data were collected through interview, observation and document analysis and analyzed following Miles and Hubberman's Interactive Model. Furthermore, the results showed that the teachers mostly had positive beliefs about Scientific Approach for English teaching, even though there were also a few negative beliefs about it too. Moreover, most of their positive and negative beliefs were reflected in their teaching. However, there were also some inconsistencies found between what they admitted to believe and what were shown in the implementation. Keywords:, Beliefs, Scientific Approach and practices